Digestibility Quality of Elephant Grass (Pennisetum purpureum) and Concentrate with The Addition of Urea Molasses In Vitro - Armina Fariani; Anggriawan Naidilah Tetra Pratama; Gatot Muslim; Lili Warly (Universitas Bengkulu, 2022)
This study aimed to study the digestibility quality of Elephant Grass (Pennisetum purpureum) and concentrate with the addition of urea molasses in vitro. The study was conducted in vitro using an experimental method. The design used was a completely randomized design (CRD) with four treatments and five repetitions: T0 (Elephant Grass 100%), T1 (Elephant Grass 60% + 40% Concentrate), T2 (Elephant Grass 60%) % + Umos 40%) T3 (Elephant Grass 60% + Concentrate 20% + Umos 20%). The results showed no effect (P>0.05) of the combination treatment on dry matter digestibility. Meanwhile, T2 and T3 treatments affected the fermentation quality, including VFA, NH3, total gas production, and methane gas concentration.